Application Of Alexander Principle ‘Driftodontics’ Mechanics To 1st Premolar Extraction Cases Compared To 1st Premolar Extraction Cases Treated with Conventional MBT System- An Assessment - Dhakar, Neelam; Joneja, Purva; Mishra, Samvit; Priyadarshini, Maitreye; Shwetneel, Shwetneel; Faraz, Sameen (Journal of Neonatal Surgery, 2025)
Background- Inspite of the tremendous improvements in technology that allow for fewer patients to require extractions, there are always patients who have significant enough crowding that ultimately necessitate the removal of premolars. Alleviating the lower anterior crowding prior to placement of the fixed appliances shortens the time in braces, and allows self correction by natural drift. One such treatment strategy which allows all this is Driftodontics. Potential benefits from a period of physiologic dental drift post-extraction, was proposed by Bourdet. “Driftodontics” is a term that can be attributed to Dr. R.G. “Wick” Alexander in his textbook. The benefits include shorter period of fixed appliance therapy because of unprompted alignment of the teeth, oral hygiene problems due to appliance therapy decreases because of less time period of appliance in the oral cavity and the dentoalveolar support also increases. Objective- 1.To measure and compare the apical root resorption in mandibular anterior teeth in 1st premolar extraction cases selected on the basis of anterior crowding irregularity index treated with Driftodontics and MBT system cases (Angle’s class 1, class 2 division 1and class 2 division 2 malocclusions). To compute and compare the clinical mobility in mandibular anterior teeth in 1st premolar extraction cases treated with Driftodontics and MBT system cases. 3.To calculate and compare the total number of appointments and overall chairside time taken in both study groups. Methodology- This is an In-vivo and In-vitro cross-sectional study with examination which includes the measurement of apical root resorption in mandibular anterior teeth on IOPAs (RVGs) by using modified Lind’s method and measuring the mobility of mandibular anterior teeth based on Miller’s mobility index on patients undergoing orthodontic treatment with driftodontics from alexander principles and conventional MBT system. Data is collected by taking Pretreatment and Post-retraction records and also by recording the number of appointments as well as chair side time. Result- The t-value (6.903) and p-value (0.000)* indicate a statistically significant difference, showing that Driftodontics required fewer appointments than Conventional MBT. The p-values for all teeth were below 0.05, confirming statistically significant differences in root resorption, showing reduced root resorption in driftodontics than conventional MBT. p-values for mobility being statistically significant (ranging from 0.007 to 0.034)**. This indicates that Conventional MBT causes significantly more post-treatment tooth mobility compared to Driftodontics, reinforcing that Driftodontics provides a more stable post-treatment outcome. Conclusion- This study suggests that Driftodontics may provide a more efficient treatment approach, reducing the burden on patients in terms of time and frequency of visits, more comfortable, reduce dentoalveolar stress, showing reduced root resorption, decreased post retraction mobility and shows more stable post retraction outcome. Hence, the study shows that Driftodontics is more advantageous and comfortable than Conventional MBT